Hubungan Menstruasi dan Kadar Hemoglobin dengan Motivasi Belajar pada Mahasiswi D3 Kebidanan - Esty Puji Rahayu (Journal of Ners and Midwifery, 2017)
The nutritional problems in Indonesia that still need serious attention from all parties include: lack of vitamin A, iodine deficiency disorders,anemia, and growth disorders.Factors affecting Hb levels in girls are blood loss caused by menstrual bleeding, lack of Fe in the food consumed, chronic diseases, changing patterns of young women from previously organized to less regular, an imbalance between nutritional intake and Activities performed. Lack of Hb levels is the cause of anemia. Lazy, often sleepy and weakness is one of the effects of low Hb levels. A student who is anemic, less motivated to learn so less can produce high achievement. The research design uses correlational analytic method with cross-sectional approach. In this study population is all female D3 midwifes 2nd semester academic year 2015-2016. Sampling in this research is done by using simple random sampling. The questionnaire used to measure learning motivation was a validated questionnaire was taken from Pintrich et.al's A Manual for the Use of the Motivated Strategies for Learning Questionnaire (MSLQ) of 30 items. Data of menstruation relationship with learning motivation using Chi Square test with result of menstrual relationship with learning motivation with p = 0,003 (p <0,05). The correlation of Hb level with learning motivation was analyzed using Spearman Rank Test test with the result of correlation between Hb level with learning motivation p = 0,036 (p <0,05)Keyword :Â The nutritional problems in Indonesia that still need serious attention from all parties include: lack of vitamin A, iodine deficiency disorders,anemia, and growth disorders.Factors affecting Hb levels in girls are blood loss caused by menstrual bleeding, lack of Fe in the food consumed, chronic diseases, changing patterns of young women from previously organized to less regular, an imbalance between nutritional intake and Activities performed. Lack of Hb levels is the cause of anemia. Lazy, often sleepy and weakness is one of the effects of low Hb levels. A student who is anemic, less motivated to learn so less can produce high achievement. The research design uses correlational analytic method with cross-sectional approach. In this study population is all female D3 midwifes 2nd semester academic year 2015-2016. Sampling in this research is done by using simple random sampling. The questionnaire used to measure learning motivation was a validated questionnaire was taken from Pintrich et.al's A Manual for the Use of the Motivated Strategies for Learning Questionnaire (MSLQ) of 30 items. Data of menstruation relationship with learning motivation using Chi Square test with result of menstrual relationship with learning motivation with p = 0,003 (p <0,05). The correlation of Hb level with learning motivation was analyzed using Spearman Rank Test test with the result of correlation between Hb level with learning motivation p = 0,036 (p <0,05)Keyword : menstruation, Hb, studies motivation